(untitled) (LACCEI, 2024)
From the review of the articles, it is confirmed that the insertion of renewable energies such as solar photovoltaic and wind energy, which, for the purpose of supplying the demand for electricity, contribute to reduce the greenhouse gases resulting from the environmental pollution generated by conventional power plants and thus decarbonize the electricity sector. Likewise, the State is required to implement training activities, promote a regulatory framework to encourage the massive use of renewable energies and evaluate the technical capacity of the facilities to absorb, without problems, the growth of these important projects that use natural resources